Hand puppets; how to make and use them. - Ross, Laura (New York, Lothrop, Lee & Shepard Co., 1969)
Directions and diagrams for making various types of puppets, dressing and handling them, setting up a stage, and writing and producing one's own show. Includes three puppet plays.
Bibliography: p. 189.
Keywords: Puppet plays -- Juvenile literature; Puppet theater -- Juvenile literature; Puppets -- Juvenile literature; Puppet plays